Factors Influencing Doomscrolling Behavior in Generation Z College Students Social Media Users: Scoping Review - Ariel Akbar Arditia Muhtar; Iyus Yosep; Taty Hernawaty; Suryani Suryani (Eduvest - Journal of Universal Studies, 2025)
The development of social media in Generation Z students presents the phenomenon of doomscrolling, which is the tendency to excessively search for negative content or news that impacts mental health. This study aims to map the factors that affect doomscrolling behavior in Generation Z students who use social media through scoping reviews. Article searches were conducted on PubMed, Scopus, and Google Scholar using the PCC (Population, Concept, Context) framework, covering the period 2015–2025, with inclusion criteria for empirical articles in Indonesian or English that are available in full text. A total of 12 articles met the criteria and were analyzed descriptively. The results of the review showed that doomscrolling was influenced by psychological factors (stress, anxiety, depression, psychological distress, insomnia), cognitive-behavioral factors (Fear of Missing Out, social media addiction, intensity of use, digital multitasking), personal factors (self-control, self-efficacy, emotion regulation, neurotic personality), and socio-technological factors (low social support and social media algorithms that reinforce exposure to negative content). Doomscrolling has consistently been associated with decreased mental well-being and increased emotional fatigue. These findings confirm the importance of digital literacy interventions, emotion regulation training, and strengthening self-control for Generation Z students.